Development of Interactive Digital Comics Based on Gamification to Improve Komering Cultural Literacy in Junior High Schools of OKU Timur - Nindy Devita Sari; Fisnia Pratami; Widya Dhara; Vella Julia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to develop an interactive digital comic based on gamification to enhance Komering cultural literacy among junior high school students in Ogan Komering Ulu Timur Regency. The research employed a Research and Development (R&D) method using the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation, involving 35 students as trial participants. The digital comic product was presented in an interactive video format equipped with gamified quizzes. The results indicated a significant improvement in cultural literacy, with an average pre-test score of 2.21 and a post-test score of 3.23. Paired-sample t-test results showed t = 12.4; df = 34; p < 0.001, with a Cohen’s d effect size of 2.09 (very large). These findings suggest that the gamification-based interactive digital comic is valid, practical, and effective as a learning medium for Komering local culture content. This study has implications for cultural preservation through interactive media utilization and provides a development model that can be replicated in other regional cultural contexts.